Pengaruh Karakteristik Akun Instagram terhadap Kepemimpinan Opini dan Dampaknya terhadap Pemilihan Destinasi Wisata - Wenes, Gufran; Kusumah, Ahmad Hudaiby Galih; Rosita, Rosita (Tourism and Hospitality Essentials Journal, 2023)
The development of technology, especially the internet and social media, has significantly impacted human decision-making habits, including in the tourism industry. Instagram has become the main platform for influencers to disseminate information and recommendations, particularly related to travel destinations. This study aims to explore the influence of Instagram account characteristics on travel destination choices by followers of tourism influencers on the platform. A quantitative approach with descriptive technique analysis and Partial Least Squares (PLS) was used to identify the relationship between Instagram account characteristics, opinion leadership, and destination choices. The analysis results showed that perceived uniqueness and perceived originality of Instagram accounts significantly influence influencer opinion leadership, which, in turn, affects the destination choices of their followers. These findings provide valuable insights for the tourism industry and influencer marketing on social media platforms.